Maatilan talouskeskuksen toiminnallinen ja maisemallinen suunnittelu - Kivinen, Tapani (MTT, 2005)
Maatilojen rakennuksia on suunniteltu ja rakennettu vaiheittain tarpeen mukaan. Tämä on johtanut eri-ikäisten, muotoisten ja väristen rakennusryhmien muodostumiseen. Maatilojen talouskeskusten hahmosta välittyy sukupolvien työn tulos ajallisesti kerrostuneina rakennusmassoina. Siinä piilee niiden kansanomainen viehätys. Tila- ja yksikkökoon kasvun myötä tuotantoa jatkavilla maatiloilla on merkittäviä uudisrakennustarpeita. Uusien suurten tuotantorakennusten sijoittelu vanhaan pienimittakaavaiseen tilakeskukseen luo uudenlaiset haasteet, joita ei ole käsitelty viimeisten kahden vuosikymmenen aikana. Maatilojen talouskeskuksia tulee suunnitella määrätietoisesti pitkän aikavälin projektina niin, että varaudutaan myös tulevaisuuden laajentumiselle. Samalla pitää huolehtia siitä, että uudisrakentaminen sopii ympäristöönsä. Kasvava talouskeskus alkaa muistuttaa pientä yhdyskuntaa, jota pitää kehittää maatilamittakaavaan soveltuvalla ympäristösuunnittelulla. Tätä uutta suunnittelutyökalua voidaan kutsua maatilojen talouskeskusten maankäyttösuunnitteluksi tai kaavoittamiseksi. Se tarkoittaa uudisrakentamistarpeiden tunnistamista ja rakennusmassojen sijoittelun hahmottelua pitkän aikavälin suunnitelmaksi. Yksikertaisimmillaan se voi olla asemapiirros tai havainnekuva talouskeskuksesta 10 tai 20 vuoden kuluttua. Suunnitelman keskeiset ainekset koostuvat tilan tuotannollisista tavoitteista, nykyisen tilakeskuksen toiminnallisista ominaisuuksista, uudisrakentamisen sijoittelumahdollisuuksista sekä uudisrakentamisen soveltuvuudesta lähi- ja kaukomaisemaan. Uudisrakentamisessa tulee mahdollisuuksien mukaan hyödyntää vanhan rakennusperinteen henki sekä hallita vanhan ja uuden välinen mittakaavaero. Rakennusten massoittelun ja mittakaavallisten kysymysten hallitsemiseksi tietokoneen avulla tapahtuva kuvallinen virtuaalimallinnus on helppo ja hyödyllinen työkalu suunnittelijan, tilaajan ja lupaviranomaisen välisessä keskustelussa, kun ympäristöön parhaiten sopivaa vaihtoehtoa arvioidaan.

Farm buildings have gradually been planned and built over decades according to the needs and demands of production. Farmsteads consequently have buildings of different ages, colours and appearances. The overall shape of a Finnish farmstead tells us of the work done by the past generations. The architecture of a farmstead comprises historical layers of different periods, styles and technologies, which is why they look picturesque and cosy. The number of active farms is continuously declining and the unit size is growing. The growing farms have significant needs for larger production buildings. Farmstead planning faces great challenges in trying to set new large-scale buildings among the old small-scale production buildings and dwellings. However, these challenges have not been addressed during the last two decades. Those farms remaining in the farming business need a long-term land-use plan to develop the farmstead as a built environment. A growing farmstead resembles a small community and needs to be designed as such with proper design practises and tools. One new tool is farmstead design using urban planning methods. This means that a farm must have a vision of future production and a strategy for survival in a national and global economy, which provides a basis for the needs of new buildings. Farmstead design is a combination of economic planning and building design with a long-term view. Farmstead design makes plans for the future - for the next 10 or 20 years - so that the next generation can expand. The essential ingredients of a farmstead plan are functional characteristics together with environmental aspects and landscape architecture. The spirit of an old farmstead should be maintained, meaning the unity of the colour spectrum and material choices. The scale difference between the new and old buildings may be problematic and must be carefully considered. The greatest challenge is to ensure that new buildings blend and fit together with the old buildings. A simple long-term farmstead plan is expected to be an unofficial and non-bureaucratic tool. In a simple form it can be an illustrative site plan or a map showing new buildings expected for the next 20 years. The documentation may vary but the goal is important: a farmstead with a clear vision of where future buildings and production yards will be situated, how the farm infrastructure will be developed, how the microclimate is to be utilized and how the farmstead façade will fit with the harmonious landscape architecture in close up and long distance views. Virtual modelling is a new practical tool allowing building designers to illustrate new buildings in their actual environments. It is a photo montage technology using modern computer programmes and digital photographs and cad files. Together, they provide a simple and rapid method for planners, customers and authorities to decide between good and not so good site alternatives for new buildings.
Keywords: Ko; Ra; Ma; kotieläintilat; maatilat; rakennussuunnittelu; maaseudun suunnittelu; sikalat; navetat; livestock farms; farms; rural planning; piggeries; cattle sheds